2019
DOI: 10.15761/icst.1000326
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng extract and its constituents alleviate cisplatin toxicity and reverse cisplatin resistance

Abstract: Cisplatin (DDP) is one of most used anticancer agents. It has shown antitumor activity in testicular cancer, head and neck cancer, ovarian cancer, lung cancer, malignant lymphoma and bladder cancer. It causes much toxicity such as skin and mucous membranes toxicity, ototoxicity and nephrotoxicity especially at higher dose, which might be involved with DNA damage and subsequently renal cell death. Ginseng is a group of cosmopolitan plants. As the root of Panax ginseng C.A. Meyer, ginseng is well known as a toni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that ginseng and its ingredients such as ginsenoside metabolite could alleviate toxicity, reverse resistance, and enhanced the effects of platinum-based agents against lung cancer cells. 10,11 A systematic review with meta-analysis has also stated that ginsenoside complemented the efficacy and reduced drug-induced toxicity from chemotherapy. 12 Nevertheless, even with additional meta-analyses, the evidence remains limited and inconclusive for the efficacy of ginsenoside as an effective adjuvant for platinum-based chemotherapy of NSCLC patients.…”
mentioning
confidence: 99%
“…Previous studies have reported that ginseng and its ingredients such as ginsenoside metabolite could alleviate toxicity, reverse resistance, and enhanced the effects of platinum-based agents against lung cancer cells. 10,11 A systematic review with meta-analysis has also stated that ginsenoside complemented the efficacy and reduced drug-induced toxicity from chemotherapy. 12 Nevertheless, even with additional meta-analyses, the evidence remains limited and inconclusive for the efficacy of ginsenoside as an effective adjuvant for platinum-based chemotherapy of NSCLC patients.…”
mentioning
confidence: 99%
“…Panax quinquefolium L., also known as American ginseng, is a perennial herb from the family Araliaceae [1]. The beneficial effects of American ginseng products, such as antitumor and anti-inflammatory activities, immunity-improving effects, and blood-sugarreducing activities, are mainly attributed to bioactive ingredients such as ginsenosides, polyphenols, and polysaccharides [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Active hexose correlated compound (AHCC) is a dietary supplement with a well-known immune stimulating effect, and there is a report of AHCC use maintaining remission in a breast cancer patient [15]. Ginseng extract contains numerous phytochemicals that have significant pharmacological activities, and Cai, Zhang and Huang (2019) [16] reviewed the data showing that ginseng extract and its constituents are promising candidates for cisplatin toxicity prevention and the reversal of resistance. Intermittent fasting has also been recognized as an anticancer strategy.…”
mentioning
confidence: 99%